Efforts to Improve Learning Outcomes in Integrated Science Through an Integrative Learning Model for Fifth-Grade Elementary School Students - Irsa Nofrianti; Mahluddin Mahluddin; Sean Popo Hardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study attempts to enhance the learning results of Natural and Social Sciences (IPAS) by implementing an integrative learning paradigm with fifth-grade students in SDN 132/VII Sungai Bemban. The planning, execution, observation, and reflection phases of Classroom Action Research (CAR) were carried out. 27 students served as research participants, and learning outcome tests, observation, and recording were used to gather data. The study's findings suggest that using an integrative learning model can improve students' comprehension and involvement throughout the educational process. Both the percentage of learning completion and student learning outcomes rose with each cycle. Additionally, fifth-grade students' IPAS learning outcomes were successfully enhanced by the integrative learning model since it allowed them to connect it to real-world situations. Additionally, this model can serve as a substitute for contextual and creative teaching methods in elementary schools.